On energy wave equations with non-negative non-linear terms. (June 2016) - Milla Miranda, M.; Louredo, A.T.; Clark, M.R.; Clark, H.R.
Abstract: This paper deals with the existence of at least one solution and the uniform stabilization of the energy of an initial-boundary value problem for a non-linear wave equation with non-linear boundary condition of the feedback type. The non-linearities in both waves and boundary equations behave as functions of the type | u | R ϱ for ϱ > 1 . Abstract : Highlights: Results on existences of global solutions. Special conditions where there is uniqueness of solutions. One rate of uniform stability for the energy.